The prevalence and clinical outcome of supraventricular tachycardia in different etiologies of pulmonary hypertension - Fingrova, Zdenka; Ambroz, David; Jansa, Pavel; Kuchar, Jan; Lindner, Jaroslav; Kunstyr, Jan; Aschermann, Michael; Linhart, Ales; Havranek, Stepan (PloS one, 2021)
PURPOSE: Patients with pulmonary hypertension (PH) frequently suffer from supraventricular tachycardias (SVT). The main purpose of our study was to identify the cumulative incidence of SVT in patients with different etiologies of PH. The secondary objective was to analyse the clinical impact of SVT. METHODS: We retrospectively studied the prevalence of SVT and the clinical outcome in 755 patients (41% males; 60 ± 15 years; mean follow-up 3.8 ± 2.8 years) with PH of different etiologies. The prevalence of SVT was analysed separately in isolated pre-capillary PH (Ipc-PH) and in patients with combined post- and pre-capillary PH (Cpc-PH). RESULTS: The prevalence of SVT in the Ipc-PH group (n = 641) was 25% (n = 162). The most prevalent arrhythmias were atrial fibrillation followed by a typical atrial flutter (17% and 4.4% of all Icp-PH patients). An excessive prevalence of SVT was found in patients with pulmonary arterial hypertension associated with congenital heart disease (35%, p = 0.01). Out of the overall study population, Cpc-PH was present in 114 (15%) patients. Patients with Cpc-PH manifested a higher prevalence of SVT than subjects with Ipc-PH (58; 51% vs. 162; 25%; p <0.0001) and were more likely to have persistent or permanent atrial fibrillation (38; 29% vs. 61; 10%; p <0.0001). Parameters significantly associated with mortality in a multivariate analysis included age, male gender, functional exercise capacity and right atrial diameter (p < 0.05). Neither diagnosis of SVT nor type of arrhythmia predicted mortality. CONCLUSIONS: The study detected a significant prevalence of SVT in the population of PH of different origins. Different spectrum and prevalence of arrhythmia might be expected in different etiologies of PH. Patients with an elevated post-capillary pressure showed a higher arrhythmia prevalence, predominantly due to an excessive number of atrial fibrillations. The diagnosis of SVT was not associated with mortality.
Keywords: Female; Aged; Prevalence; Tachycardia, Supraventricular; plicní hypertenze; Humans; ženské pohlaví; výsledek terapie; mužské pohlaví; senioři; lidé; supraventrikulární tachykardie; lidé středního věku; Hypertension, Pulmonary; Male; Middle Aged; Treatment Outcome; prevalence